Could Investors’ Attention in News Hunting Affect the International Capital Market? - Sukamulja, Sukmawati; Thedora, Stefanny (The Indonesian Capital Market Review, 2023)
The study of investors’ attention while making decisions in the capital market focuses on some spe- cific keyword searches in the leading search engine platform, namely Google Search Volume Index. This is because investors need to gather related information for the efficiency and effectiveness of their decision-making process. This study aims to provide empirical evidence regarding the effect of investors’ attention on the rate of return, trading activity, and volatility. It offers a new broad perspec- tive on the international capital market, which is projected as the key player in the global economy in the upcoming years, representing both developing and developed countries. The GARCH model was applied to examine how volatile and residual variants are affected by previous residual variants of the variables. This study conducts robustness tests by expanding the scope time of data to enhance these research findings into weekly and monthly periods. The final robust, but not uniform, result was seen in one uncategorized country.